2022
DOI: 10.1152/jn.00070.2022
|View full text |Cite
|
Sign up to set email alerts
|

GluN3 subunit expression correlates with increased vulnerability of hippocampus and entorhinal cortex to neurodegeneration in a model of temporal lobe epilepsy

Abstract: Temporal lobe epilepsy (TLE) is the most common type of epilepsy in adults that is often refractory to anti-epileptic medication therapy. Neither the pathology nor the etiology of TLE are fully characterized, although recent studies have established that the two are causally related. TLE pathology entails a stereotypic pattern of neuron loss in hippocampal and parahippocampal regions, predominantly in CA1 subfield of the hippocampus and layer 3 of the medial entorhinal area (MEA), deemed hallmark pathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…To validate our imaging data in the MEA, we also assayed the hippocampus where GluN3A expression was established using area specific tissue analysis (ASTA) ( Beesley et al, 2022 ). Consistent with these studies, we found widespread expression of GluN3A protein puncta that colocalized with PSD-95 throughout CA1 to CA3 ( Figure 2A ), although the high magnification used for their visualization precluded quantification of their relative abundance in these subfields.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To validate our imaging data in the MEA, we also assayed the hippocampus where GluN3A expression was established using area specific tissue analysis (ASTA) ( Beesley et al, 2022 ). Consistent with these studies, we found widespread expression of GluN3A protein puncta that colocalized with PSD-95 throughout CA1 to CA3 ( Figure 2A ), although the high magnification used for their visualization precluded quantification of their relative abundance in these subfields.…”
Section: Resultsmentioning
confidence: 99%
“…By assaying the spatial expression of their subunit proteins (GluN1, GluN2A, GluN2B, and GluN3A) using area-specific tissue analysis (ASTA), a novel methodology for harvesting brain chads from hard-to-reach regions within brain slices for Western blotting, we recently showed that GluN3A was expressed in a gradient along the mid-lateral extent of layer three MEA and along the CA1-subicular axis in the hippocampus, unlike GluN1 and GluN2A which were uniformly distributed. The expression profile of GluN3A defined the “zones of vulnerability” in these regions where there was significant cell loss and neurodegeneration, hallmark features of the disease ( Beesley et al, 2022 ). Thus, the GluN3A expression pattern was indicative of the spatial extent of the pathology in the hippocampus and entorhinal cortex implicating t -NMDARs in TLE pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The predominance of GluN2B-containing NMDARs with reduced expression of GluN2A was observed in ventral hippocampus and cortex areas of rats in pilocarpine-induced model of epilepsy [69], while increase in the total NMDARs number due to overexpression of GluN1 and GluN2A or GluN2B was revealed after PTZ-induced status epilepticus [70]. Epilepsy-induced neurodegeneration accompanied by incorporation of GluN3A subunits to NMDARs resulted in formation of triheteromeric receptors which possess increased selectivity for Ca 2+ over Na + and make the neurons more susceptible to excitotoxic damage [71,72]. On the other hand, the works [73][74][75]…”
Section: Discussionmentioning
confidence: 99%